Re-evaluation of the interprofessional collaboration scale validation between nurses towards other health care professionals occupied in Italian emergency medical services - Carradore, Marco; Guasconi, Massimo; Giusti, Gian Domenico; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Interprofessional collaboration (IPC) between health professionals is fundamental for the provision of an efficient and effective medical care service. This is especially so in states of emergency, as highlighted by the ongoing coronavirus disease 2019 pandemic. This study aimed to obtain further evidence regarding the validity and reliability of the Italian language IPC scale –an instrument for measuring interprofessional collaboration– in a setting that has yet to be investigated at an in-depth level: the emergency departments in Italian hospitals.Methods: The survey tool was a structured questionnaire in the Italian language. It comprised the validated Italian version of the IPC scale plus a question concerning the frequency of collaborations between the nurses interviewed and other health professionals. Confirmatory factor analysis was applied to rate the three factors (“communication”, “accommodation” and “isolation”) that compose the scale.Results: Four hundred thirty-six nurses working in an emergency department for at least one year completed the questionnaire, which assessed collaboration with other health professionals working in the same department. The model fit statistics are satisfactory for all the nurse-target group combinations analysed. Regarding the Cronbach’s alpha statistic used to compute the reliability of the scale, acceptable values were obtained for all items, except for those related to the isolation factor for each case of interprofessional collaboration considered.Conclusions: The results confirm the validity of the IPC scale as an instrument for the assessment of interprofessional collaboration involving nurses and other workers occupied in the provision of healthcare in Italian emergency departments.